2004
DOI: 10.1111/j.1752-1688.2004.tb01017.x
|View full text |Cite
|
Sign up to set email alerts
|

IMPLICATIONS OF ON‐GROUND NITROGEN LOADING AND SOIL TRANSFORMATIONS ON GROUND WATER QUALITY MANAGEMENT1

Abstract: This paper presents a modeling approach based on a geographic information system (GIS) to estimate the variability of on‐ground nitrogen loading and the corresponding nitrate leaching to ground water. The methodology integrates all point and nonpoint sources of nitrogen, the national land cover database, soil nitrogen transformations, and the uncertainty of key soil and land use‐related parameters to predict the nitrate mass leaching to ground water. The analysis considered 21 different land use classes with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 52 publications
0
38
0
1
Order By: Relevance
“…It was reported that this approach of developing a 3-D hydrostratigraphic model can be applied to other areas having complex aquifer systems, and is also useful in helping lay audiences visualize aquifer systems. Almasri and Kaluarachchi (2004) presented a GIS-based modeling approach to estimate the variability of on-ground nitrogen loading and the corresponding nitrate leaching to groundwater. The methodology integrates all point and nonpoint sources of nitrogen, the national land cover database, soil nitrogen transformations, and the uncertainty of key soil and land use-related parameters to predict the nitrate mass leaching to groundwater.…”
Section: Ramlingam and Santhakumarmentioning
confidence: 99%
“…It was reported that this approach of developing a 3-D hydrostratigraphic model can be applied to other areas having complex aquifer systems, and is also useful in helping lay audiences visualize aquifer systems. Almasri and Kaluarachchi (2004) presented a GIS-based modeling approach to estimate the variability of on-ground nitrogen loading and the corresponding nitrate leaching to groundwater. The methodology integrates all point and nonpoint sources of nitrogen, the national land cover database, soil nitrogen transformations, and the uncertainty of key soil and land use-related parameters to predict the nitrate mass leaching to groundwater.…”
Section: Ramlingam and Santhakumarmentioning
confidence: 99%
“…In general, the main nitrogen sources in agricultural watersheds include dairy and poultry manure, dairy lagoons, applications of fertilizers on agricultural fields and lawns, atmospheric deposition, irrigation with nitrogen-contaminated ground water, septic tanks, and nitrogen fixed by legumes (Almasri and Kaluarachchi, 2004a-c). The abovementioned nitrogen sources are spatially allocated using the NLCD except for septic tanks and dairy lagoons where GIS point shapefiles are utilized to assign the corresponding loadings (Almasri and Kaluarachchi, 2004a).…”
Section: Nitrogen Sources and Simulation Of Nitrate Contaminationmentioning
confidence: 99%
“…It also does not bind to soil particles like many water contaminants do. As a result, it easily leaches through the soil due to infiltration of rainfall or irrigation water [8,9].…”
Section: Introductionmentioning
confidence: 99%